Pengaruh Iklim Organisasi dan Kepuasan Kerja Terhadap Kinerja Guru Bimbingan dan Konseling - Micha Felayati Silalahi; Daharnis Daharnis; Alizamar Alizamar (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
This research measuring counseling teacher performance  from the climate organization, job satisfaction as well as the influence them on counseling teacher performance. This research used to quantitative method with corelation descriptive.. The subject of this research was the counseling teachers senior high schooling Padang were 72, that selected by stratified random sampling. An instrument consisted of three variables and using model scale Likert. Research conducted analyze dusing linear regression simple and multiple linear regression. Research findings shows that: (1) on average a snapshot of counseling teacher performance has medium category, climate organization and job satisfaction has at medium category, (2) there was positive and significant relationship between climate organization and counseling teacher performace, (3) there was positive and significant relationship between job satisfaction on the of counseling teacher performance, (4) there was positive and significant relationship between climate organization and job satisfaction together on the counseling teacher performance.